ANTHROPOMORPHIC TERRACOTTA STATUETS OF THE SOUTH DAGESTAN OF ALBANO-SARMATIC PERIOD - Gadziev, M S; Bakusev, M A (History, Archeology and Ethnography of the Caucasus, 2016)
The terracotta female figurines from the burial ground Sharakun and the Derbent settlement (Southern Dagestan) are considered in the article. Authors, basing on an archaeological context date the figures from the Derbent settlement to the first centuries AD (not later than the middle of 3rd century AD). Anthropomorphous figurines obviously represent the stylized image of the goddess of fertility, the patroness of agriculture, mother-keeper of grain, bread and reflect the existing agrarian cult developing in the conditions of significant progress of complex agricultural and cattle breeding economy of the region. Figurines meet in monuments of the Early Bronze Age and Albano-Sarmatian period of Dagestan and demonstrate the similar processes, which took place in the religious sphere during the periods of development of agricultural culture.